2015
DOI: 10.1038/srep17567
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of ALPPS procedure in a rat model

Abstract: Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) has been reported to be a novel surgical technique that provides fast and effective growth of liver remnant. Despite occasional reports on animal studies, the mechanisms of rapid liver regeneration in ALPPS remains unclear. In the present study, we intend to develop a reproducible rat model to mimick ALPPS and to explore the underlying mechanisms. Rats assigned to the portal vein ligation (PVL), left lateral lobe (LLL) resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…The role of inflammatory cytokines was also demonstrated by Yao et al [35], who found increased levels of TNF-α (tumor necrosis factor-α), IL-6 (interleukin-6), and HGF (hepatocyte growth factor) after ALPPS upon comparison with the PVL group. Supportive of these findings is a report by Shi et al [36] who found elevated NF-κB (nuclear factor-κ light chain enhancer of activated B cells), p65, STAT3 (signal transducer and activator of transcription 3), and YAP (yes-associated protein) expressions after ALPPS; these mediators have a cardinal role in cell cycle induction and maintenance, and also have strong downstream interplay with the main inflammatory cytokines.…”
Section: Operative Techniquementioning
confidence: 56%
See 3 more Smart Citations
“…The role of inflammatory cytokines was also demonstrated by Yao et al [35], who found increased levels of TNF-α (tumor necrosis factor-α), IL-6 (interleukin-6), and HGF (hepatocyte growth factor) after ALPPS upon comparison with the PVL group. Supportive of these findings is a report by Shi et al [36] who found elevated NF-κB (nuclear factor-κ light chain enhancer of activated B cells), p65, STAT3 (signal transducer and activator of transcription 3), and YAP (yes-associated protein) expressions after ALPPS; these mediators have a cardinal role in cell cycle induction and maintenance, and also have strong downstream interplay with the main inflammatory cytokines.…”
Section: Operative Techniquementioning
confidence: 56%
“…Their biological properties provide favorable conditions for research by reason of their great regenerative capacity and stress tolerance, making rodents ideal for surgical research. With respect to ALPPS, however, rodents seem to be less ideal for research purposes, although they may provide valuable data for answers to basic research questions as shown in the publications of Schlegel et al [34], Yao et al [35], or Shi et al [36]. On the other hand, certain data collected from rodent research cannot be directly applied to humans owing to the undeniable differences in general physiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data revealed that time-dependent factors appear to be the major source of variation in post-injury alterations of gene expression in liver regeneration. Early transcriptomic changes and the upstream regulators after all the procedures included cell cycle associated genes (E2F1, CCND1, FOXM1, TP53, and RB1), transcription factors (Myc, E2F1, TBX2, FOXM1) [23][24][25][26][27][28] , DNA replication regulators (CDKN1A, EZH2, RRM2) 29 , G1/S-transition regulators (CCNB1, CCND1, RABL6) 30 , cytokines and growth factors (CSF2, IL-6, TNF, HGF, VEGF, and EGF) 9,16,31,32 . At the cellular level, this corresponds to the transition from the quiescent G0 phase to active mitosis.…”
Section: Discussionmentioning
confidence: 99%